Management of the patient with diabetes and coronary artery disease: a contemporary review. (May 2013) - Raymond, Timothy; Raymond, Russell; Lincoff, A Michael
Diabetes mellitus is a metabolic disease with microvascular and macrovascular complications, and is well known to increase the risk of coronary atherosclerosis. Despite recent reductions in the prevalence of coronary artery disease and cardiovascular events in the USA, persons with diabetes remain up to four-times as likely to die of cardiovascular disease than the general population. Diabetes is associated with an atherogenic lipid profile, induces a hypercoagulable state, and increases coronary plaque volume, progression and instability. Medicinal and procedural treatments in the patient with diabetes should be multifactorial, targeting and managing the many coexisting risk factors that contribute to atherosclerosis. This type of treatment is complex and should be individualized, and guided by a careful review of recent literature. Here we discuss important clinical data and their impact on up-to-date recommendations for the management of coronary artery disease in the patient with Type 2 diabetes mellitus.